An analytical closed-form solution for multiple line supplier selection problem. Issue 4 (4th July 2019) - Pearn, W. L.; Tai, Y. T.; Tseng, S. C.
Abstract: Supplier selection is an essential issue, particularly, for semiconductor manufacturing. Nowadays, since high demands in the globally competitive semiconductor manufacturing environment, multiple-line processes are quite commonly applied. In the paper, we consider a two-stage method composing of quality verification and selection decision for multiple-line supplier selection problems. Since quality performance is an important criterion in supplier selection, we test whether the new supplier has a significantly better capability than the existing supplier based on the multiple-line yield index C pk M in the stage of quality verification. In selection decision, when the magnitude of capability outperformance is significant, switching contracts to a new entrant supplier is suggested. In addition, analytical closed-form solutions for asymptotical critical values and required sample sizes are derived and tabulated for the investigated multiple-line supplier selection problem. We demonstrate the applicability of the proposed supplier selection method by presenting a real-world example taken from a semiconductor packaging shop floor located in the Science-based Industrial Park in Hsinchu, Taiwan.